Population variation and natural selection on leaf traits in cork oak throughout its distribution range - Ramírez-Valiente, José Alberto; Valladares, Fernando; Sánchez-Gómez, David; Delgado, Antonio; Aranda, Ismael (Acta Oecologica, 2014)
A central issue in evolutionary biology is the exploration of functional trait variation among populations and the extent to which this variation has adaptive value. It was recently proposed that specific leaf area (SLA), leaf nitrogen concentration per mass (Nmass) and water use efficiency in cork oak play an important role in adaptation to water availability in the environment. In order to investigate this hypothesis, we explored, first, whether there was population-level variation in cork oak (Quercus suber) for these functional traits throughout its distribution range; if this were the case, it would be consistent with the hypothesis that different rainfall patterns have led to ecotypic differentiation in this species. Second, we studied whether the population-level variation matched short-term selection on these traits under different water availability conditions using two fitness components: survival and growth. We found high population-level differentiation in SLA and Nmass, with populations from dry places exhibiting the lowest values for SLA and Nmass. Likewise, reduced SLA had fitness benefits in terms of growth for plants under dry conditions. However, contrary to our expectations, we did not find any pattern of association between functional traits and survival in nine-year-old saplings despite considerable drought during one year of the study period. These results together with findings from the literature suggest that early stages of development are the most critical period for this species. Most importantly, these findings suggest that cork oak saplings have a considerable potential to cope with dry conditions. This capacity to withstand aridity has important implications for conservation of cork oak woodlands under the ongoing climate change.
Keywords: Adaptation; Nitrogen leaf content; Phenotypic selection; Population divergence; Specific leaf area; water use efficiency

Can net photosynthesis and water relations provide a clue on the forest decline of Quercus suber in North Tunisia? - Lee, S. H.; Woo, S. Y.; Nasr, Z. (African Journal of f Biotechnology, 2011)
Net photosynthesis, sap flow density (SFD) and water use efficiency (WUE) were measured in a Quercus suber forest in north Tunisia in an attempt to explain the forest decline. In general, sap flow was positively related to light intensity and water loss, indicating that high light intensities can increase the SFD up to the saturation point in the cork oak. CO2 assimilation of cork oak in this region was light intensity-dependent. Cork oak showed a general increase in photosynthetic rates with increasing light intensity up to the light saturation point. Increased radiation probably increased the photosynthesis and growth above ground in this area, whereas the below-ground soil had insufficient moisture for uptake through the roots because the high light intensity and temperature induced high evapotranspiration.
Keywords: decline; evaportranspiration; light intensity; Quercus suber; sap flow density; water use efficiency

Ecophysiological Traits Associated with Drought in Mediterranean Tree Seedlings: Individual Responses versus Interspecific Trends in Eleven Species - Valladares, F; Sánchez-Gómez, D (Plant Biology, 2006)
Abstract: Species differ regarding their drought tolerance and individuals of a given species can modify their morphology and physiology in response to drought. However, since evolutionary and ecological selective pressures differ, individual and interspecific responses to drought might not match. We determined summer survival and a number of ecophysiological variables in two factorial experiments with seedlings of eleven tree species present in Mediterranean ecosystems, grown under slowly imposed water stress and control conditions. Plants experiencing drought exhibited reduced growth, low specific leaf area, chlorophyll content, and photosynthetic rate when compared to the controls, and species-specific drought tolerance was associated with an analogous set of trait values. However, while species with high leaf area ratio and shoot-root ratio exhibited greater drought tolerance, drought induced the reversed response within species. Contrary to expectations, water use efficiency was lower in drought-tolerant species and decreased in water-stressed individuals compared to the control plants. There was a distinctive phylogenetic signal in the functional grouping of species, with oaks, pines, and other genera being clearly different from each other in their drought tolerance and in their functional responses to drought. However, all relationships between ecophysiological variables and drought tolerance were significant after accounting for phylogenetic effects, with the exception of the relationship between drought tolerance and photochemical efficiency. Our results show that drought tolerance is not achieved by a single combination of trait values, and that even though evolutionary processes and individual responses tend to render similar results in terms of functional traits associated with drought, they do not necessarily match.
Keywords: Drought tolerance; functional traits; Mediterranean plants; phylogeny; water use efficiency; woody seedlings

Ecophysiological Traits Associated with Drought in Mediterranean Tree Seedlings: Individual Responses versus Interspecific Trends in Eleven Species - Valladares, F.; Sánchez-Gómez, D. (Plant Biology, 2006)
Abstract: Species differ regarding their drought tolerance and individuals of a given species can modify their morphology and physiology in response to drought. However, since evolutionary and ecological selective pressures differ, individual and interspecific responses to drought might not match. We determined summer survival and a number of ecophysiological variables in two factorial experiments with seedlings of eleven tree species present in Mediterranean ecosystems, grown under slowly imposed water stress and control conditions. Plants experiencing drought exhibited reduced growth, low specific leaf area, chlorophyll content, and photosynthetic rate when compared to the controls, and species-specific drought tolerance was associated with an analogous set of trait values. However, while species with high leaf area ratio and shoot-root ratio exhibited greater drought tolerance, drought induced the reversed response within species. Contrary to expectations, water use efficiency was lower in drought-tolerant species and decreased in water-stressed individuals compared to the control plants. There was a distinctive phylogenetic signal in the functional grouping of species, with oaks, pines, and other genera being clearly different from each other in their drought tolerance and in their functional responses to drought. However, all relationships between ecophysiological variables and drought tolerance were significant after accounting for phylogenetic effects, with the exception of the relationship between drought tolerance and photochemical efficiency. Our results show that drought tolerance is not achieved by a single combination of trait values, and that even though evolutionary processes and individual responses tend to render similar results in terms of functional traits associated with drought, they do not necessarily match.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Drought tolerance; functional traits; Mediterranean plants; phylogeny; water use efficiency; woody seedlings

Effects of the interaction between drought and shade on water relations, gas exchange and morphological traits in cork oak (Quercus suber L.) seedlings - Aranda, I.; Castro, L.; Pardos, M.; Gil, L.; Pardos, J. a (Forest Ecology and Management, 2005)
The combined effect of drought and light on different physiological and biochemical traits was assessed in cork oak (Quercus suber L.) seedlings grown under two levels of light availability and submitted to a long-standing drought. Watering was withdrawn after germination and seedlings were allowed to dry to a water content of ca. 50% of ﬁeld capacity. At this point, water-stressed seedlings were grown under moderate drought and two light regimes: high light (HL—50%) and low light (LL— 2%). Soil water in control plants was kept close to ﬁeld capacity (90–100%) for both light environments. Water-relations parameters derived from P–V curves, gas exchange and water status at predawn (Cpd ) were evaluated at twice during the experiment. Nitrogen and chlorophyll contents were determined in the same leaves used for the gas exchange measurements. In addition, maximum rate of carboxylation (Vcmax) and electronic transport (Jmax) were derived from A–Ci curves in well-watered seedlings. The variation on moisture availability during the experiment was the same under both light environments. In control plants, Cpd was over 0.3 MPa at the two harvests, while stressed seedlings decreased to 0.9 MPa, with no differences between light treatments. Water stress decreased osmotic potentials at full (Cp100 ) and zero turgor (Cp0 ). The regressions between both potentials and Cpd showed a higher intercept in shade grown seedlings. This fact will point out the higher osmoregulation capacity in sun seedlings whatever water availability. Nitrogen investment on a per leaf mass (Nmass ), chlorophyll content (Chlmass ) and SLA tended to show a typical pattern of sun-shade acclimation. Thus, the three parameters increased with shade. Only for Nmass there was a signiﬁcant effect of watering, since water stress increased Nmass . LL plants showed a lower photosynthetic capacity in terms of maximum net photosynthesis at saturating light (Amax), which was related to a decrease in Vcmax and Jmax . Both parameters varied with speciﬁc leaf area (SLA) in a similar way. The low-light environment brought about a higher nitrogen investment in chlorophyll, while under high-light environment the investment was higher in carboxylation (Vcmax) and electronic transport ( Fmax). Stomatal conductance to water vapour (gwv ) and Amax were lower in low-light seedlings independently of watering. In addition, there was a trend to keep higher intrinsic water use efﬁciency (IWUE) under high light environment. The increase of IWUE under water stress was higher in HL seedlings. This was as consequence of the steeper decline in gwv as Cpd decreased. The decrease of Amax with Cpd occurred in a similar way in LL and HL seedlings. Thus, the HL seedlings tended to sustain a higher ability to increase IWUE than LL seedlings when they were submitted to the same water stress.
Keywords: Cork oak; Drought; light; osmotic adjustment; photosynthesis; water use efficiency

Establishment of co-existing Mediterranean tree species under a varying soil moisture regime - Lloret, Francisco; Penuelas, Josep; Ogaya, Romà (Journal of Vegetation Science, 2004)
We investigated the responses of two co-existing Mediterranean trees with different regeneration strategies (Phillyrea latifolia seedlings and Quercus ilex sprouts) to experimental drought below the forest canopy. We considered different recruitment stages and used leaf isotopic discrimination to estimate water use efficiency (WUE) and nitrogen availability and use. Drought decreased the emergence and survival of seedlings and sprouts. Survival and growth of older saplings were not influenced by drought. Seedling emergence of P. latifolia was higher than Q. ilex sprout production, but Q. ilex sprouts had higher survival and growth rates. These differences disappeared in the sapling stage. Carbon isotopic discrimination suggested that Q. ilex sprouts had higher WUE than P. latifolia seedlings. Drought increased WUE of recruits, particularly in Q. ilex. Water use regulation increased with ageing, particularly in P. latifolia. Q. ilex had higher δ15N values than P. latifolia; these were also higher under drier soil conditions. Current year seedlings had higher δ15N than saplings, particularly in P. latifolia, suggesting they exploit superficial soil layers. These results suggest that sprouts obtain benefit from resources stored in parent plants. At earlier stages, they perform better than seedlings. This response is not coupled to adult vulnerability to drought for these species, revealing the difficulty of predicting species dynamics during climate change.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: climate change; Drought; mediterranean forest; Nitrogen use; phillyrea latifolia; Quercus ilex; Recruitment; Regeneration; Seedling; sprouting; water use efficiency